(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Iron deficiency anemia is a disease characterized by impaired hemoglobin synthesis due to a lack of iron in the blood plasma and bone marrow and, as a consequence, impaired trophic development of organs and tissues. 211 patients (patients aged 28 to 43 years) with inflammation of the maxillofacial area applied to the Department of Maxillofacial and Plastic Surgery of the BOMMC. Of the 211 patients, 118 were included in the study group, and the remaining 93 were included in the control group. Of the 211 patients, 64 patients had purulent phlegmon of the lower jaw on the left, 52 patients had purulent phlegmon of the upper jaw, 51 patients had purulent periostitis of the upper jaw, 44 patients had purulent periostitis of the lower jaw. diagnosis of retromolar purulent periostitis. Patients of the main group were recommended to rinse the mouth with a decoction of covulla root 10 times a day and, along with the traditional treatment regimen, drink Gyno-Tardiferon. After taking Gyno-Tardiferon, the patients’ sleep improved, they became more alert and active, the hyperemic conditions at the incision sites disappeared (as a result of stabilizing the supply of oxygen to the tissues), and a decoction prepared from the roots, leaves and forge seeds has an analgesic, antibacterial, antiseptic and passivating effect of active microflora, occupy a positive place in restoring the health of patients.